DIMENSIONS OF VALUE FROM AXIOLOGICAL BARRIERS FOR THE SCIENTIFIC MANUSCRIPT - Argota-Pérez, George (2023)
The aim of the study was to analyze dimensions of value in the scientific manuscript. The study was conducted between May and July 2021, where  the ScienceDirect database was accessed. The last fi ve years of viewing was fi ltered and only the article publication types referred to the review and research. Through means of a systematic random probability sampling, 25 research articles were selected. 5% of the citations for each of the scientific articles of selection were analyzed and then the interpretation from the scientific problematization, statistical model of the selection variables, act and power of the scientific argumentation for four axiological barriers of dimensions of value that identify the scientific publication. It was observed in the scientific articles that the value dimensions of the axiological barriers showed coding of accepted responses. Likewise, the need to understand a hermeneutical key of the scientific manuscript is shown and with this, the search for the scientific effort for its recognition from how the manuscript should be written is considered. It is concluded that the dimensions of value from axiological barriers make it possible to understand the nature of the impact of scientific articles, since they determine the methodological domain of scientific research and its way of communicating it; however, the contributing analysis and guide for its probable publication is guaranteed from the hermeneutics of questions for each scientific manuscript. Keywords: research characteristics – methodological processes – scientific publication – scientific writing